2019
DOI: 10.1093/conphys/coz088
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia during incubation does not affect aerobic performance or haematology of Atlantic salmon (Salmo salar) when re-exposed in later life

Abstract: Hypoxia in aquatic ecosystems is becoming increasingly prevalent, potentially reducing fish performance and survival by limiting the oxygen available for aerobic activities. Hypoxia is a challenge for conserving and managing fish populations and demands a better understanding of the short- and long-term impacts of hypoxic environments on fish performance. Fish acclimate to hypoxia via a variety of short- and long-term physiological modifications in an attempt to maintain aerobic performance. In particular, hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…It remains unclear how long the effects of early exposure to hypoxia or warming can persist through later life stages of fishes. For example, early developmental exposure to hypoxia did not confer lasting effects on hypoxia tolerance, acclimation capacity or aerobic metabolic performance in juvenile Atlantic salmon reared in hypoxia when tested after 8–15 months in normoxia ( Wood et al , 2017 ; Wood et al , 2020 ). However, even if the persistent effects observed in this study do not carry-over to later juvenile stages, the persistent effects we observed in performance at the fry stage can still impact individual survival in the river.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear how long the effects of early exposure to hypoxia or warming can persist through later life stages of fishes. For example, early developmental exposure to hypoxia did not confer lasting effects on hypoxia tolerance, acclimation capacity or aerobic metabolic performance in juvenile Atlantic salmon reared in hypoxia when tested after 8–15 months in normoxia ( Wood et al , 2017 ; Wood et al , 2020 ). However, even if the persistent effects observed in this study do not carry-over to later juvenile stages, the persistent effects we observed in performance at the fry stage can still impact individual survival in the river.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, through metabolic measurements by swimming trials, it was suggested that especially smaller salmon (200 g) may be more vulnarable to hypoxia (50%) than their larger counterparts (3.5 kg; Oldham et al, 2019). Exposure to hypoxia from fertilization until start feeding did not appear to influence tolerance to hypoxia later in life (Wood et al, 2019(Wood et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Then, it decreased to 94 ng/L at the final experiment, closing the normal limit of fish glucose at 40 -90 mg/L [36]. The alteration of the Hb value and the increase in glucose highlighted the stress condition in fish [19,37,38]. In addition to DO, exposure to ammonia also stimulate a significant decrease in hematological parameters [39], which occur in blower treatment with ammonia concentration exceeding 1 mg/L.…”
Section: Fish Performancementioning
confidence: 99%